In Praise of the Garrison Mentality: Why Fear and Retreat May be Useful Responses in an Era of Climate Change - Malisch, Sherrie (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (University of New Brunswick, Dept. of English, 2014)
This essay revisits one of the foundational settler texts of Canadian literature, Northrop Frye’s “Conclusion” to the Literary History of Canada. It offers a controversial re-reading of Northrop Frye’s infamous “garrison mentality” thesis from the perspective of contemporary eco-criticism, particularly in view of the global crisis of climate change. The essential ecological logic of Frye’s account is that human isolation from nature impedes humanity’s “fullest functioning as a species.” However, the logic of the garrison thesis has been implicitly shared by critics who purport to oppose Frye’s approach; at base, both Frye and his critics assume that human-nature interconnection fosters human potential and creativity. Drawing on a number of prominent environmental biologists and ecocritics, the essay demonstrates that the garrison mentality, in which humans maintain a respectful distance from nature, may be the most ecologically sound response. This opens up a provocative question: “What if the most crucial role for literature . . . is not to fuel and thrive on the individual quest for creative fulfillment and self-understanding, but to harness itself to the task of bringing human aspirations, collectively, within limits?”